OPTIMIZATION OF ENZYMATIC HYDROLYSIS CONDITIONS FOR ANTIBACTERIAL PEPTIDES PRODUCTION AGAINST PANTOEA SPP. CAUSING RICE LEAF BLIGHT - Jamal, Siti Norazura; Udie Lamasudin, Dhilia; Muhialdin, Belal J.; Saidi, Noor Baity; Kok Song , Lai; Yusof, Mohd Termizi (Malaysian Journal of Science, 2024)
The Central Composite Design (CCD) within the Response Surface Methodology (RSM) was applied to optimize the enzymatic hydrolysis process. This process used Alcalase® to hydrolyze Bactronophorus thoracites protein with the goal of maximizing its antimicrobial effects. Four distinct parameters were identified as independent variables: pH (A: 8.5–10.5), temperature (B: 45–65 °C), hydrolysis time (C: 120–360 min), and enzyme-to-substrate ratio (D: 1.45%–2.65% w/v). Meanwhile, the antimicrobial activity was chosen as the response variable, specifically against Pantoea ananatis (Y1) and Pantoea stewartii (Y2). According to the findings, the constructed quadratic polynomial model showed a significant correlation with the experimental data, as evidenced by the coefficient of determination (R2) values for antimicrobial activity: Y1 being 0.9893 (p < 0.0001) and Y2 at 0.9848 (p < 0.0001). Optimal antimicrobial activity for Bactronophorus thoracites protein hydrolysates (BTPH) was recorded at 46.748% against P. ananatis and 40.768% against P. stewartii. This result was observed under the optimal conditions of pH 9.5, temperature 55ºC, hydrolysis duration of 240 minutes, and 2.05% w/v enzyme-to-substrate ratio. There was a notable alignment between the actual and predicted values from our models, with the Residual Standard Error (RSE) values falling under 5%. Furthermore, the established Minimum Inhibitory Concentration (MIC) was 250µg/mL, and the Minimum Bactericidal Concentration (MBC) was 500µg/mL for both P. ananatis and P. stewartii. In conclusion, the findings suggest that the refined BTPH has great promise as an effective bioactive component for agricultural use.